Effect of lipids complexes on controlling ethylene gas release from V-type starch - Liu, Zhanpeng; Wang, Shaokang; Chin, Ping Tan; Bin, Zhang; Fu, Xiong; Huang, Qiang (Elsevier, 2022)
In this study, the effects of n-decanoic acid (n-CA) or coconut oil (CCN) on the release of ethylene from V-type starch (VS) were investigated. Results of differential scanning calorimetry showed that adding n-CA or CCN into VS generated a starch–lipid complex. Results of scanning electron microscopy and confocal laser scanning microscopy indicated that VS granules aggregated but oil films appeared on the surface of the VS aggregates when oil was added. The addition of n-CA or CCN effectively delayed the release of ethylene in VS, and the deceleration effect gradually became obvious with the increase in oil addition. These results suggest that the formation of starch–lipid complexes, the aggregation of starch granules, and the presence of oil films play important roles in slowing down the release of ethylene.